Redesigning Delivery: Boosting Adoption of Coffee Management Practices in Uganda. The climate smart investment pathway approach and the farmer segmentation tool - Jassogne, Laurence T.P.; Mukasa, David; Bukomeko, Hannington; Kemigisha, Elizabeth; Kirungi, Diana; Giller, Onno; Asten, Piet J.A. van (2017)
Coffee is an important crop for the Ugandan economy, as it earns the country US$415 million in foreign export revenues and supports 1.7 million smallholder farmers (UCDA, 2016). Nevertheless, coffee yields have stagnated for over a decade, despite concerted efforts to improve productivity. Climate change is increasing the pressure on the sector, and the effects are already being felt. Climate smart agricultural (CSA) practices are being promoted as a means to help farmers cope with climate change. The CSA training package focuses on planning good agricultural practices in a way that the changing climate is taken into consideration. The training package for coffee consists of a large number of practices (soil and water conservation, tree management, quality of coffee, among others), and is currently provided all in one go as a complete package. This approach is cumbersome and not aligned to pertinent needs of coffee farmers, as coffee is a perennial crop and needs continuous care throughout the year. To address the need for better targeting of practices, this Info Note presents two complementary approaches: the climate smart investment pathways (CSIPs) and farmer segmentation. The CSIPs break down the full training package of CSA practices into more manageable subsets of practices. These smaller packages are aimed at being more aligned with the structural (resource endowments) and functional (entrepreneurship) characteristics of different types of farmers. CSIPs build up a sequential and incremental approach to implementing the practices. The farmer segmentation tool differentiates the coffee farmers into different groups, based on their assets and entrepreneurial characteristics. These segmentations will help advise the relevant stakeholders that support farmers on how to best engage with and train farmers in the most relevant practices (based on the CSIP) by taking their capacity and willingness to implement the practices into consideration. This Info Note will first go through the development process of the CSIPs, based on the results from a study on Robusta coffee systems in Luweero and Nakasongola. Then it will move onto the process and results of the farmer segmentation work done in the Greater Luweero region (which encompasses Luweero and Nakasongola). The implications of this work will be discussed and recommendations will be made for further work and use of these methods.